"Actions Speak Louder Than Words": Korean American Emerging Adults' Perceptions and Meaning Making of Their Parents' Instrumental Aspects of Parenting. (February 2018) - Kang, Hyeyoung; Shih, Kristy
Drawing on semistructured interviews, this study explored 25 Korean American emerging adults' experience of their parents' parenting, focusing on the aspects of parenting they perceive as salient as well as their perceptions and interpretations of such experiences. The majority of our respondents highlighted instrumental aspects of their parents' parenting which includes different ways that their parents provide instrumental tools for their well-being and success, such as material provision and service for children. Importantly, they attributed significant meaning to these parental actions. Youth's recognition of and appreciation for their parents' instrumental aspects of parenting was shaped by the immigrant family context as well as an increase in cultural understanding and perspective taking of their parents. Taken together, this study suggests the importance of examining sociocultural contexts of family processes to better understand experiences of youth from diverse immigrant and cultural groups.